1998
DOI: 10.1007/s002449900419
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects of Sodium Acetate/Formate Deicer, Ice Shear™

Abstract: The environmental impacts of Ice Sheartrade mark, an alternative highway deicer, have been evaluated using standard laboratory tests; biochemical oxygen demand (BOD) tests, chemical oxygen demand (COD) tests, acute rainbow trout bioassays, and phytotoxicity tests were used. Ice Shear consists of equimolar sodium acetate and sodium formate. The organic matter of the deicer can be readily degraded microbiologically in the natural environment with a slow rate of degradation at lower temperatures but an increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Synowiecki and Al-Kateeb [13] stated that a good chitin purification method should insure effective removal as well as utilization of other shell components. Alkaline salts of carboxylic acids had been found to have good de-icing ability [20][21][22] as well as good antimicrobial activity [23][24] . Acetate salts (mainly calcium, magnesium and potassium acetates) can be used as environmentally friendly de-icing agents and lactate salts (mainly calcium and potassium lactates) can be used as food preservatives.…”
Section: Production Of Deicing Agent/ Food Preservativementioning
confidence: 99%
See 1 more Smart Citation
“…Synowiecki and Al-Kateeb [13] stated that a good chitin purification method should insure effective removal as well as utilization of other shell components. Alkaline salts of carboxylic acids had been found to have good de-icing ability [20][21][22] as well as good antimicrobial activity [23][24] . Acetate salts (mainly calcium, magnesium and potassium acetates) can be used as environmentally friendly de-icing agents and lactate salts (mainly calcium and potassium lactates) can be used as food preservatives.…”
Section: Production Of Deicing Agent/ Food Preservativementioning
confidence: 99%
“…Acetate ion Potassium acetate Bang and Johnston [21] stated that a deicing agent is known to be more effective when it has a lower molecular weight with higher solubility. Table 6 shows the solubilities of sodium chloride,calcium lactate and some acetate salts.…”
Section: Production Of Deicing Agent/ Food Preservativementioning
confidence: 99%
“…Traditionally, formic acid is used as a preservative and an antibacterial agent in livestock feed, the production of leather, and the dyeing and finishing of textiles. Sodium/calcium formate has also found recent use as an environmentally friendly de‐icer . Numerous recent studies have demonstrated that formic acid can be used directly to power fuel cells .…”
Section: Introductionmentioning
confidence: 99%
“…To mitigate these harmful effects, alternatives such as calcium-magnesium acetate (CMA) has been considered [ 8 , 9 ]. Acetate-based salts have the similar melting snow or ice efficiency to that of chloride, and they are less harmful for the surrounding environment [ 10 12 ]. Nevertheless, it cannot melt snow or ice sustainably on the asphalt pavement, because rain or melted snow will wash the acetate anions (Ac - ).…”
Section: Introductionmentioning
confidence: 99%